Emerged Coral Reefs Record Holocene Low‐Angle Normal Fault Earthquakes. Issue 20 (21st October 2020) - Biemiller, James; Taylor, Frederick; Lavier, Luc; Yu, Tsai‐Luen; Wallace, Laura; Shen, Chuan‐Chou
Abstract: Low‐angle normal faults (LANFs; dip <30°) accommodate kilometers of crustal extension, yet it remains unclear whether these faults can host large earthquakes or if they predominantly creep aseismically. Most active LANFs typically slip at rates of <3 mm/year. Here, we report U‐Th ages from a series of distinct levels of formerly shallow‐living corals killed by uplift‐induced emergence of the footwall of one of the world's fastest‐slipping LANFs, the Mai'iu fault in Papua New Guinea, which slips at rates of 8–12 mm/year. Coral ages and coastal morphology indicate punctuated episodic uplift events consistent with seismic slip on the Mai'iu fault. Maximum episodic uplift increments of 0.5–1.8 m imply earthquakes of M w  > 7. We present the first coral paleoseismological record of normal fault earthquakes, which constrain the timing and surface uplift patterns of multiple LANF seismic cycles and confirm that LANFs can slip in large ( M w  > 7) earthquakes. Plain Language Summary: The Earth's crust breaks along fractures and faults, including "normal faults, " where tectonic plates pull apart. Subsequent slip on these faults enables plates to move away from each other and can occur via slow fault creep or infrequent fast earthquakes. Although normal faults typically intersect the surface of the Earth at a steep angle, some low‐angle normal faults intersect the Earth's surface at a shallower angle. It remains unclear whether these faults typically creep gradually or slip in large earthquakes because active low‐angle normal faults are uncommon and slip at low long‐term slip rates. This study uses uplifted fossilized coral reefs to reconstruct the timing and style of fault slip near one of the world's fastest‐slipping low‐angle normal faults, the Mai'iu fault in Papua New Guinea. Isotopic and geomorphological evidence from corals killed by fault‐related coastal uplift show that the Mai'iu fault slips infrequently and episodically, revealing a history of large earthquakes in this region. Key Points: U‐Th dating of emerged coral reefs confirm active tectonic uplift at rates of 1.6–2.9 mm/year along the southern Goodenough Bay coastline Sequences of preserved reef platforms and eroded sea level notches indicate that coastal uplift is episodic Episodic uplift increments >1 m imply M w  > 7.0 earthquakes with slip on a shallowly dipping segment of the Mai'iu‐Goodenough normal fault